Perbedaan Motivasi Belajar Siswa Laki-Laki dan Perempuan di SMAN 22 Surabaya - Alief Rizqi Arian; Yohana Wuri Satwika (Asosiasi Riset Ilmu Kesehatan Indonesia, 2025)
The purpose of this study was to determine whether there are differences in the learning motivation of male and female students at SMAN 22 Surabaya. This study used quantitative approach. The subjects in this study were male and female students of SMAN 22 Surabaya with a total of 165 students. Where with details of 67 male students and 98 female students consisting of 3 batches. This research uses descriptive data analysis techniques. Based on the results of data analysis and previous discussion, it is known that the significance value is 0.984> 0.05, it means that there is no significant difference in learning motivation in both male and female students. In the data analysis above, the mean or average of male students, 102.3731, is greater than that of female students, 102.3367. so it can be stated that the learning motivation of male students is greater than that of female students.